2014
DOI: 10.1007/s13197-014-1629-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various techniques on biochemical characteristics and bitterness of pummelo juice

Abstract: The consumer acceptability of pummelo juice is affected badly due to the presence of bitter principles in it. Therefore in order to avoid such bitterness development, the extracted juice from pummelo was subjected to five different treatments like juice diffused into syrup (70°Brix), lye peeling of segments in boiling NaOH for 2-3 min, increasing the pH of juice, hot water treatment (50°C) prior to peeling for 20 min and without any treatment (control) for suppressing the development of bitterness in the juice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…Limonoid is the other major type of bitter compound in addition to naringin in citrus fruit, including nomilin and limonin [8,24]. A study has shown that generally limonoids accumulate relatively high at young fruit or fruit expanding stage and then fall to very low in concentration or under detectable levels in mature fruit [36].…”
Section: Citlgtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limonoid is the other major type of bitter compound in addition to naringin in citrus fruit, including nomilin and limonin [8,24]. A study has shown that generally limonoids accumulate relatively high at young fruit or fruit expanding stage and then fall to very low in concentration or under detectable levels in mature fruit [36].…”
Section: Citlgtsmentioning
confidence: 99%
“…Although flavor is favored differently for different individuals, there is a generally accepted notion of good taste which is attributed to an appropriate balance of sweetness and sourness in citrus [7]. Excessive bitterness and the delayed bitterness in citrus pose great challenge for the citrus industry to provide consumers readily acceptable fresh fruit and citrus juice, thus causing great lose in citrus market value [8]. Extremely sour and acidic can destroy the sweet taste of citrus and may be physiologically harmful to humans.…”
Section: Introductionmentioning
confidence: 99%
“… 47 Furthermore, the fruit juice prepared from the pulp is rich in antioxidant and polyphenolic compounds such ferulic acid, hesperidin, caffeic acid, naringin, p-coumaric acid, and vanillic acid were reported to be present in the fruit juice. 33 , 44 , 48 51 Current chemical, medical, and pharmacological literature has confirmed various pharmacological activities as well as nutritional value of the indigenous fruit and so a compendious review of the plant is established.…”
Section: Plant Introductionmentioning
confidence: 99%
“…The pomelo juice has the prime bittering component, such as naringin, narirutin, neoeriocitrin, eriocitrin, neohesperidin, and hesperidin, with a level of 245.63-393.96 mg/L which are not desirable in fruit processing industries as they reduce the consumer acceptability (Pichaiyongvongdee & Haruenkit, 2009). Processing techniques like blanching (Zid et al, 2015), application of adsorptive materials, for example, cellulose triacetate (Chandler & Johnson, 1977) and cellulose esters (Barmore et al, 1986), chemical methods with the use of β-cyclodextrin (Konno et al, 1981), resins (Gupta et al, 2020;Kola et al, 2010;Mishra & Kar, 2003;Singh et al, 2016), mixed with sugar syrup (Kore & Chakraborty, 2015), lye peeling (Kore & Chakraborty, 2015), pH adjustment (Kore & Chakraborty, 2015), hot water treatment (Kore & Chakraborty, 2015), and the combination of sucrose and citric acid (Guadagni et al, 1974) were employed for debittering. Polystyrene divinylbenzene, resin (Mishra & Kar, 2003), poly (vinyl alcohol) (PVA), and cryogel (Busto et al, 2007) were also used successfully for the removal of bitterness from the juices; however, the physical and chemical methods are not always welcomed by the juice processing industries, as these techniques had several drawbacks including loss of chemical components like acidity, vitamin C, and soluble solids.…”
Section: Introductionmentioning
confidence: 99%